Photo-Oxidation of Various Organic Compounds, Including Pollutants, by Europium (III) in Fuel Cell Systems - Felix Blind; Stefan Fränzle (ChemEngineering)
The ongoing anthropogenic climate crisis necessitates a reassessment of numerous technical domains, including the energy sector. An alternative to conventional fuel cells is provided by photo fuel cells, which possess at least one photoactive electrode (e.g., TiO2). However, it should be noted that such fuel cells are often constrained in terms of the range of potential fuels that can be utilized. Considering prior research on the distinctive photochemistry of europium, it was hypothesized hypothesis that a photocell based on the photo-oxidation of diverse organic compounds by trivalent europium might be theoretically feasible. As demonstrated in multiple experiments, it is feasible to construct and operate a fuel cell utilizing these diverse, straightforward substrates. In this context, peak powers of up to 14 μW have already been observed with the fuel cell described. It is noteworthy that an average electrical power of up to 6.28 μW was observed over a period of 168 h (7 days). Furthermore, it was demonstrated that simple alcohols (ethanol) could be completely oxidized with trivalent europium under suitable conditions. From various studies with different ethanol concentrations, it could be seen that a certain amount of water was needed to break down simple alcohols and organic compounds in general.